The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1001/jamaoto.2017.2235
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neurocognitive Deficits With Radiotherapy or Chemoradiotherapy for Patients With Head and Neck Cancer

Abstract: Head and neck cancer survivors have neurocognitive sequelae up to 2 years after definitive chemoradiotherapy or radiation treatment. Patients and health care teams should know about such potential risks. Further research is warranted in search of strategies to avoid, reduce, and compensate for declines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 31 publications
(54 reference statements)
6
50
0
Order By: Relevance
“…With regard to focal CRT, studies have found the midline and medial temporal structures of the brain, especially the hippocampus and hypothalamus, to be more vulnerable to radiotherapy, although these regions are not as likely to have been exposed during radiation for STS. Nevertheless, neurocognitive deficits have been reported in patients with adult‐onset head and neck cancer after treatment with chemotherapy and/or radiation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to focal CRT, studies have found the midline and medial temporal structures of the brain, especially the hippocampus and hypothalamus, to be more vulnerable to radiotherapy, although these regions are not as likely to have been exposed during radiation for STS. Nevertheless, neurocognitive deficits have been reported in patients with adult‐onset head and neck cancer after treatment with chemotherapy and/or radiation …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, neurocognitive deficits have been reported in patients with adult-onset head and neck cancer after treatment with chemotherapy and/or radiation. 29 Having a moderate to severe neurologic condition was associated with both worse neurocognitive performance and poor HRQOL. The most common neurologic condition was peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal assessments of these participants, 67 both head and neck cancer and noncancer cohorts, are currently ongoing. Our findings suggest that objective cognitive functioning in patients with head and neck cancer is not impaired before treatment relative to healthy individuals, although subjective symptoms are, including cognition, fatigue, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Still, multiple demographic factors, such as education level, smoking exposure, and history of concussion, are associated with a patient's risk of cognitive disturbance before treatment. Longitudinal assessments of these participants, 67 both head and neck cancer and noncancer cohorts, are currently ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a risk for second primaries in HNSCC associated with cigarette smoking and excessive alcohol consumption . The aims of HNSCC follow‐up are early detection of recurrences and second primaries to enhance the chances for successful salvage therapy, the detection and management of treatment‐related sequelae, and psycho‐social support for the patients . However, the ideal structure of follow‐up is a matter of ongoing debate.…”
Section: Introductionmentioning
confidence: 99%